Effect of base analog substitutions in the specific GATC site on binding and methylation of oligonucleotide duplexes by the bacteriophage T4 Dam DNA-[N6-adenine] methyltransferase. - Malygin, E G (1999)
The interaction of the phage T4 Dam DNA-[N6-adenine] methyltransferase with 24mer synthetic oligonucleotide duplexes having different purine base substitutions in the palindromic recognition sequence, GATC, was investigated by means of gel shift and methyl transfer assays. The substitutions were introduced in either the upper or lower strand: guanine by 7-deazaguanine (G-->D) or 2-aminopurine (G-->N) and target adenine by purine (A-->P) or 2-aminopurine (A-->N). The effects of each base modification on binding/methylation were approximately equivalent for both strands. G-->D and G-->N substitutions resulted in a sharp decrease in binary complex formation. This suggests that T4 Dam makes hydrogen bonds with either the N7- or O6-keto groups (or both) in forming the complex. In contrast, A-->P and A-->N substitutions were much more tolerant for complex formation. This confirms our earlier observations that the presence of intact 5'-G:C base pairs at both ends of the methylation site is critical, but that base substitutions within the central A:T base pairs show less inhibition of complex formation. Addition of T4 Dam to a complete substrate mixture resulted in a burst of [3H]methylated product. In all cases the substrate dependencies of bursts and methylation rates were proportional to each other. For the perfect 24mer k cat = 0.014/s and K m = 7.7 nM was obtained. In contrast to binary complex formation the two guanine substitutions exerted relatively minor effects on catalytic turnover (the k cat was reduced at most 2. 5-fold), while the two adenine substitutions showed stronger effects (5- to 15-fold reduction in k cat). The effects of base analog substitutions on K m(DNA) were more variable: A-->P (decreased); A-->N and G-->D (unchanged); G-->N (increased).